Efectos de la densidad de siembra en la producción de Palma aceitera (Elaeis guineensis Jacq, 1897) en el Ecuador - Hurtado Murillo, Yomira Alexandra (2022)
Planting density can increase biomass production and crop yield in oil palm, due to the increase in leaf area index and leaf length. The use of good agricultural practices that are provided to the oil palm crop provide favorable situations for the expression of the best yield capacity; among these practices is the management of planting density, since the size and length of the photosynthetic area are associated with the yield of the oil palm crop. The information obtained was analyzed, synthesized and summarized in order to inform the reader about the effects of planting density on oil palm (E. guineensis) production in Ecuador. From the above, it was determined that there is a direct relationship between planting density and the nutrients absorbed by the plants due to their consumption for production. In high quantities of plants per hectare will need larger amounts of fertilizers for their production. In order to establish an adequate planting density in oil palm cultivation, the same process that includes the determination and marking of points where the plants will be planted must be carried out for alignment and staking. It starts with the North-South orientation within the planting site, a mother line is drawn, whose length will depend on the length and width of the area. In Ecuador, the 9 x 9 planting system is usually used with 143 plants/ha with the staggered planting system. Compact palm varieties are established at 8.24 m between plants and 7.80 m between rows, with a density of 159 plants/ha. Guineensis palms are established at a distance of 9 m between plants and 8 m between rows, for a stocking density of 138.88 plants/ha. The hybrid oil palm species were established at a distance of 9.61 m between plants and 8.5 m between rows with a planting density of 81.68 plants/ha.